Analyzing leadership skills and competencies in facilitating PepsiCo's transition to a flexible organizational structure - Jian Hua, Zeng; LI, LE; Ismail, Noor Azlin; Yao Hui, Chen (International Journal of Science and Research, 2023)
This research seeks to critically assess the pivotal leadership skills and competencies required to drive and support PepsiCo's transformation towards a more flexible and adaptive organizational framework. In an ever-evolving business landscape, the ability of leaders to lead change and navigate the complexities of a flexible organization is paramount. This study aims to provide a comprehensive evaluation of the leadership attributes necessary for such a transition. Objectives: Identify the key leadership skills and competencies essential for adapting PepsiCo to a flexible organizational style. Assess the impact of leadership on organizational flexibility and agility. Examine the challenges and opportunities associated with implementing a flexible organizational structure. Offer recommendations for effective leadership strategies in PepsiCo's context. Significance: Understanding the leadership skills and competencies that facilitate organizational flexibility in a real-world context like PepsiCo can contribute valuable insights to the fields of leadership and organizational management. This research will offer practical recommendations for PepsiCo and may serve as a case study for other organizations contemplating similar transitions.